ANALISA FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI MINYAK VCO INDUSTRI KECIL WAIPIAH COCONUT DI KEC. TNS KAB. MALUKU TENGAH - Penina T. Istia; Hendriette D. Titaley; Nelda Maelissa (Soso-Q : Jurnal Manajemen, 2020)
Central Maluku is an agrarian area which has an abundance of agricultural commodities, especially the plantation sub-sector which is a trading activity in Maluku. one of the sub-sectors is coconut plantations. Coconut (CocosNucifera) is a plantation crop that is widespread in almost all regions of Indonesia. Generally, coconut plants are produced into copra which will later be used as raw materials in making coconut cooking oil. The great potential of coconut in the Sub-District of TNS (TeonNilaSerua), opens opportunities for its citizens to develop small businesses in the middle of processing virgin coconut oil (VCO). In fact, VCO produced by the community in Layeni village, Jerili village and Yafila village, is able to penetrate the consumer market even though the VCO oil production results are not widely known and known by the people of Maluku as a whole about the benefits and benefits of CVO oil produced by small business groups in TNS area.VCO production results are not too well known by consumers in the area of order. "The results of the VCO production of small businesses are marketed to the cities of Ambon, Masohi and the surrounding cities, even outside the city of Ambon, if there are advance orders to the producers. The purpose of this research is to find out the relationship between the factors that affect the production of small oil VCO industrinwaipiah coconut. The research was carried out by means of observation and interviews and conducting VCO oil production experiments. The observations are recorded, observed and analyzed using multiple regression analysis. The results obtained are the multiple regression equation is as follows: Y = 4,936 +, 063X1 +, 005X2 + (-, 522) X3 + (-, 0.49) X4. X1 = 0,000 Sig <0.05 or t arithmetic 9,928> t table 2,365, then H0 is rejected and H1 is accepted, X2 = 0.075> 0.05 or 2,086 <t table 2,365 then H0 is accepted and H1 is rejected, X3 = 0.028 <0 , 05 or t arithmetic -1.387 <t table 2.365 then H0 is accepted and H1 is rejected, X4 = 0.409 <0.05 or t arithmetic -0.887> t table 2.365 thus H0 is rejected and H1 is accepted. The raw material X1 sig 0,000 <0.05 has an impact on VCO oil production. Capital X2 sig value 0.75> 0.05 no impact on VCO oil production, Labor X3 sig value 0.208 <0.05 impact on VCO oil production, Entrepreneurship X4 sig value 0.409 <0.05 impact on VCO oil production value.Keywords: Raw materials, capital, labor, entrepreneurship in coconut oil production VCO coconut waipia TNS